Peningkatan Kompetensi Kognitif Siswa Terhadap Pemahaman Materi Kedaulatan Rakyat Dan Sistem Pemerintahan Di Indonesia Dalam Pembelajaran PKn Melalui Keterpaduan Metode Role Playing Dan Simulation Siswa Kelas X.1 SMA Negeri 1 Bengo Kabupaten Bone - Muhammad Tang (Universitas Negeri Makassar, 2019)
The problem of this research, namely whether the Civics learning outcomes of material sovereignty of the people and the system of government in Indonesia can be improved through creative simulation methods in class X.1 students of SMA 1 Bengo, Bone Regency. Based on the problems in this study, efforts were made to solve the problem of Civics learning outcomes in the matter of people's sovereignty and system of governance in Indonesia through creative simulation methods in class X.1 Bengo 1 Senior High School Bone District. The purpose of this study was to describe the improvement in Civics learning outcomes of material sovereignty and the system of government in Indonesia through creative simulation methods in class X.1 Bengo 1 Senior High School Bone District. This research is classroom action research (PTK), using a descriptive qualitative approach. The focus of this research is to improve the process and learning outcomes of Civics in the matter of people's sovereignty and the system of government in Indonesia. Data collection is done through observation and tests. The data analysis technique used is a data analysis model consisting of three activity lines, namely data reduction, data presentation and conclusion / verification. The results of the study show that creative simulation methods can improve creativity and student learning outcomes. This can be seen in the results of the study stating that the creativity of students has increased when the teacher uses the Creative Simulation Method in the lessons of the People's Sovereignty and Government System in Indonesia. This increase can be seen both in each cycle in the researched class